Shading Contributes to the Reduction of Stem Mechanical Strength by Decreasing Cell Wall Synthesis in Japonica Rice (Oryza sativa L.) - Wu, Longmei; Zhang, Wujun; Ding, Yanfeng; Zhang, Jianwei; Cambula, Elidio D.; Weng, Fei; Liu, Zhenghui; Ding, Chengqiang; Tang, She; Chen, Lin; Wang, Shaohua; Li, Ganghua (Frontiers in Plant Science, 2017)
Low solar radiation caused by industrial development and solar dimming has become a limitation in crop production in China. It is widely accepted that low solar radiation influences many aspects of plant development, including slender, weak stems and susceptibility to lodging. However, the underlying mechanisms are not well understood. To clarify how low solar radiation affects stem mechanical strength formation and lodging resistance, the japonica rice cultivars Wuyunjing23 (lodging-resistant) and W3668 (lodging-susceptible) were grown under field conditions with normal light (Control) and shading (the incident light was reduced by 60%) with a black nylon net. The yield and yield components, plant morphological characteristics, the stem mechanical strength, cell wall components, culm microstructure, gene expression correlated with cellulose and lignin biosynthesis were measured. The results showed that shading significantly reduced grain yield attributed to reduction of spikelets per panicles and grain weight. The stem breaking strength decreased significantly under shading treatment; consequently, resulting in higher lodging index in rice plant in both varieties, as revealed by decreased by culm diameter, culm wall thickness and increased plant height, gravity centre height. Compared with control, cell wall components including non-structural carbohydrate, sucrose, cellulose and lignin reduced quite higher. With histochemical straining, shading largely reduced lignin deposition in the sclerenchyma cells and vascular bundle cells compared with control, and decreased cellulose deposition in the parenchyma cells of culm tissue in both Wuyunjing 23 and W3668. And under shading condition, gene expression involved in secondary cell wall synthesis, OsPAL, OsCOMT, OsCCoAOMT, OsCCR, OsCAD2, and primary cell wall synthesis, OsCesA1, OsCesA3, OsCesA8 were decreased significantly. These results suggest that gene expression involved in lignin and cellulose in both sclerenchyma and parenchyma cells, which attribute to lignin and cellulose in culm tissue and weak mechanical tissue, consequently, result in poor stem strength and higher lodging risks.